2007
DOI: 10.1002/jts.20277
|View full text |Cite
|
Sign up to set email alerts
|

Parental response and adolescent adjustment to the september 11, 2001 terrorist attacks

Abstract: This study examined adolescents' adjustment following the attacks of September 11, 2001 (9/11). A Web-based survey was administered 2 weeks and 7 months postattacks to a national sample of adolescents (N = 104). A randomly selected parent also completed a survey at the 7-month assessment.Although exposure to the attacks was indirect, over half the participants felt threatened. Adolescents' posttraumatic stress symptoms were associated with their acute stress symptoms, parental distress, parental coping advice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 12 publications
6
88
1
Order By: Relevance
“…Prior research has indicated that parental MH influences children’s post-disaster MH (e.g., Gil-Rivas et al, 2007; Silverman & La Greca, 2002; Spell et al, 2008; Rowe et al, 2010; Valentino et al, 2010), and we explored how parental history of MH problems may moderate our models of family influences on children’s post-disaster psychopathology. Our preliminary analysis comparing hurricane exposed and non-exposed families on history of MH problems showed that hurricane exposed parents were more likely to report a history of MH problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has indicated that parental MH influences children’s post-disaster MH (e.g., Gil-Rivas et al, 2007; Silverman & La Greca, 2002; Spell et al, 2008; Rowe et al, 2010; Valentino et al, 2010), and we explored how parental history of MH problems may moderate our models of family influences on children’s post-disaster psychopathology. Our preliminary analysis comparing hurricane exposed and non-exposed families on history of MH problems showed that hurricane exposed parents were more likely to report a history of MH problems.…”
Section: Discussionmentioning
confidence: 99%
“…Children whose parents were highly distressed following natural disasters appeared to have a greater number of disaster-related problems than children whose parents were not so distressed (Gil-Rivas, Silver, Holman, McIntosh, & Poulin, 2007; Norris et al, 2002; Spell et al, 2008). MH problems can influence parents to either over- or under-estimate children’s reaction to disaster (Silverman & La Greca, 2002).…”
Section: Parental History Of Mental Health Problems As a Moderator Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…They may facilitate their children’s adjustment by providing them with suggestions for how to cope with what happened (Gil-Rivas et al 2007; Prinstein et al 1996), and by listening to their fears and concerns (Gil-Rivas et al 2007). Recently, a set of evidence-informed recommendations have been put forward, suggesting how parents should care for their children after surviving high-impact disasters (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Parents provided informational and emotional support, encouraged active involvement in preparedness and recovery efforts, positively reframed potentially negative outcomes (e.g., explaining they had insurance to rebuild homes), and adjusted their parenting style to accommodate variations in children's reactivity to the disaster. Other researchers have reported similar findings: that soothing self-talk, parental reframing, discussing emotions, and acceptance lowered children's distress levels after a disaster (Gil-Rivas et al 2007). In research on interventions with children affected by a wildfire disaster, McDermott et al (2005) have suggested that helping children, especially younger children, regulate their internal emotional states may be more important to their adjustment than the objective characteristics of the disaster event itself.…”
Section: Discussionmentioning
confidence: 67%